2002
DOI: 10.1074/jbc.m110246200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel S-Adenosyl-l-methionine:Arsenic(III) Methyltransferase from Rat Liver Cytosol

Abstract: S-Adenosyl-L-methionine (AdoMet):arsenic(III) methyltransferase, purified from liver cytosol of adult male Fischer 344 rats, catalyzes transfer of a methyl group from AdoMet to trivalent arsenicals producing methylated and dimethylated arsenicals. The kinetics of production of methylated arsenicals in reaction mixtures containing enzyme, AdoMet, dithiothreitol, glutathione (GSH), and arsenite are consistent with a scheme in which monomethylated arsenical produced from arsenite is the substrate for a second met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
216
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2
1

Relationship

6
4

Authors

Journals

citations
Cited by 323 publications
(220 citation statements)
references
References 53 publications
1
216
0
Order By: Relevance
“…We have also shown that UROtsa cells do not express AS3MT . Importantly, comparison of our previous work (Drobná et al, 2003;Lin et al, 2002;) with results of the present study suggests that serum starvation for 16 h has no effect on AS3MT expression or on the metabolic pattern of iAs in UROtsa cells.…”
Section: Discussionsupporting
confidence: 75%
“…We have also shown that UROtsa cells do not express AS3MT . Importantly, comparison of our previous work (Drobná et al, 2003;Lin et al, 2002;) with results of the present study suggests that serum starvation for 16 h has no effect on AS3MT expression or on the metabolic pattern of iAs in UROtsa cells.…”
Section: Discussionsupporting
confidence: 75%
“…An arsenic methyl transferase (As3MT) existing in a number of polymorphic forms has been identified [66][67][68]. This enzyme is crucial as a reducing agent in the methylation of iAs, and thus is at least one of the enzymes involved in this process [66,69,70].…”
mentioning
confidence: 99%
“…As V reductases may enzymatically reduce these arsenicals in mammalian tissues (4,5). Methylation of trivalent arsenicals [arsenite (iAs III ) and methylarsonous acid (MAs III )] is catalyzed by As III -methyltransferases that use S-adenosylmethionine (AdoMet) as the methyl group donor (6,7). Because MAs V and DMAs V are not toxic in acute lethality assays, methylation of iAs has long been considered a detoxification mechanism.…”
mentioning
confidence: 99%